2016
DOI: 10.1111/jphp.12598
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anticancer activity in vitro and in vivo of luteolin incorporated into long-circulating micelles based on DSPE-PEG2000 and TPGS

Abstract: DTLLM might be a potential antitumour formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The benzo(a)pyrene 50 mg/kg body weight given to mice caused elevation in lipid peroxide levels, markers of specific tumor to lungs such as carcinoembryonic antigen also called CEA and NSE or neuron‐specific enolase with an associated decrement both enzymatic antioxidants including superoxide dismutase, glutathione reductase catalase, glutathione‐s‐transferase, glutathione peroxidase, and nonenzymatic antioxidants, for example, reduced glutathione, vitamin C, and vitamin E. Luteolin treatment at 15 mg/kg body weight orally significantly offsets all these harmful alterations and thus maintained normalcy in cells. Besides, the treatment with luteolin was proposed to effectively negate benzo‐a‐pyrene‐induced enhanced regulation of the proliferating cell nuclear antigen expression, nuclear factor‐kappa B (NF‐κB), and cytochrome P450 1A1 was exposed by the evaluation of protein expression by Western bolt method (Han et al, ; Kasala, Bodduluru, Barua, & Gogoi, ; Yan, Wei, Song, Jia, & Zhang, )).…”
Section: Health Perspectives Of Tamarindmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzo(a)pyrene 50 mg/kg body weight given to mice caused elevation in lipid peroxide levels, markers of specific tumor to lungs such as carcinoembryonic antigen also called CEA and NSE or neuron‐specific enolase with an associated decrement both enzymatic antioxidants including superoxide dismutase, glutathione reductase catalase, glutathione‐s‐transferase, glutathione peroxidase, and nonenzymatic antioxidants, for example, reduced glutathione, vitamin C, and vitamin E. Luteolin treatment at 15 mg/kg body weight orally significantly offsets all these harmful alterations and thus maintained normalcy in cells. Besides, the treatment with luteolin was proposed to effectively negate benzo‐a‐pyrene‐induced enhanced regulation of the proliferating cell nuclear antigen expression, nuclear factor‐kappa B (NF‐κB), and cytochrome P450 1A1 was exposed by the evaluation of protein expression by Western bolt method (Han et al, ; Kasala, Bodduluru, Barua, & Gogoi, ; Yan, Wei, Song, Jia, & Zhang, )).…”
Section: Health Perspectives Of Tamarindmentioning
confidence: 99%
“…(NF-κB), and cytochrome P450 1A1 was exposed by the evaluation of protein expression by Western bolt method (Han et al, 2016;Kasala, Bodduluru, Barua, & Gogoi, 2016;Yan, Wei, Song, Jia, & Zhang, 2016)).…”
Section: Anticancermentioning
confidence: 99%
“…EE is an important evaluation parameter for liposomes and is affected by the amount of PC, Chol, and DSPE-PEG 2000 in the liposomes [20][21][22][23][24] . Therefore, in this study, a three-level three-factor BBD was employed to optimize the formulation variables.…”
Section: Box-behnken Designmentioning
confidence: 99%
“…Among the various types of flavonoids, luteolin (2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-4-chromenone) is a flavone in many substances, including celery, broccoli, green pepper, parsley and thyme (9). Several cellular and molecular biology studies have demonstrated that luteolin may possess anticancer activities (10,11).…”
Section: Introductionmentioning
confidence: 99%